Proceedings of the 17th International Electronic Conference on Synthetic Organic Chemistry 2013
DOI: 10.3390/ecsoc-17-b016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO nanorods modified with TPP, TPPS and Cu-TPPS for photodegradation of MB

Abstract: In this study, ZnO nanorods have been synthesized by a simple precipitation technique with zinc nitrate as starting material in the presence of ammonium hydroxide followed by calcination at 450 ˚C. Then meso-tetrakis(4-phenyl) porphyrin (TPP), meso-tetrakis(4-sulfonatophenyl) porphyrin (TPPS), and Copper meso-tetrakis(4-sulfonatophenyl) porphyrin (Cu-TPPS) have been immobilized on the ZnO nanorods and the potential of the obtained photocatalysts in degradation of methylene blue dye was studied under UV and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both the spectrum shows a characteristic peak of ZnO at 360 nm. 18,27 The incorporation of copper into zinc oxide is indicated by a shoulder peak at 450 nm in Fig. -1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the spectrum shows a characteristic peak of ZnO at 360 nm. 18,27 The incorporation of copper into zinc oxide is indicated by a shoulder peak at 450 nm in Fig. -1b.…”
Section: Resultsmentioning
confidence: 99%
“…-1b. 27 Anotherband at 619 cm -1 is assigned to the interaction between copper and oxide ion indicating the formation of Cu/ZnO nanocomposite. 200), (112), and (201) reflection planes of hexagonal ZnO respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of theZnO powders is shown in Figure 2. In the XRD patterns, a single phase of the zinc hexagonal wurtzite type was detected in the pure ZnO and cadmium doped ZnO samples, and the (101) peak was found to be the most prevalent in all patterns [11]. It was also observed that the peaks of the ZnO powder synthesized using methanol were more intense than those of the ZnO powder synthesized using ethanol [17].…”
Section: Resultsmentioning
confidence: 99%
“…Past studies have reported various techniques for modifying ZnO by doping, which resulted in products with enhanced properties and expanded applications. Rahimi et al and Lavand et al improved the optical properties of ZnO by doping with various transition metals, producing nanostructures that were suitable for photocatalysis [11,12]. Doping ZnO with narrow band-gap transition metals and non-metals is believed to be beneficial as it results in band-gap narrowing.…”
Section: Introductionmentioning
confidence: 99%